The effect of sustainability awareness on climate emotions of Chinese college students - moderated by future time perspective - Huan Cao; Peng-Fei Chen; Ke Zhang (Acta Psychologica)
Chinese college students' emotional responses to climate change are shaped by awareness of sustainability, which can be shaped by future time perspective. This study investigates the effect of sustainability awareness on climate emotions of Chinese college students, moderated by future time perspective. Drawing on value-belief-norm theory, this research examines the influences of demographic factors such as gender, college location, and educational level on sustainability consciousness and climate emotions. The questionnaire was applied to 1208 Chinese college students from eastern, central, and western China, with data analyzed using confirmatory factor analysis and hierarchical regression. Results indicate that sustainability awareness has a strong effect on climate emotions and that future time perspective may moderate this relationship to increase the effect of sustainability awareness on emotional responses to climate change. Differences also existed between gender, whereby female students reported higher levels of sustainability awareness and climate emotions than male students. Eastern Chinese students and senior students also indicated higher sustainability awareness and stronger climate emotions. These emotions contribute to understanding the psychological pathways connecting environmental beliefs with emotional engagement and offer practical implications for climate education and sustainability-focused interventions in Chinese higher education.